Food facts on the Internet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Food information on the Internet - a basic guide compiled by the Leatherhead Food Research Association and Karen Blakeman 1997 price UKL65.00